Effect of phytohormones cytokinins on the growth and development of plants - Sydorchuk, Pavlo Serhiyovych; Voronkova, Yuliia S. (My University, 2023)
The discovery of cytokinins (American scientists F. Scoot and K. Miller) is associated with research on the cultivation of callus formed from the isolated tissue of the core of a tobacco stem on a nutrient medium. Callus cells in sterile culture have been shown to stop dividing after a certain period. However, when DNA derivatives, which are formed after its autoclaving, are added to the nutrient medium, cell division is restored.
Keywords: cytokinins; callus; tobacco stem; калюс; цитокініни